2013
DOI: 10.1089/ars.2012.4958
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Sestrin 2 Controls Neuropathic Pain After Peripheral Nerve Injury

Abstract: Aims: Neuropathic pain is a chronic debilitating disease that is often unresponsive to currently available treatments. Emerging lines of evidence indicate that reactive oxygen species (ROS) are required for the development and maintenance of neuropathic pain. However, little is known about endogenous mechanisms that neutralize the pain-relevant effects of ROS. In the present study, we tested whether the stress-responsive antioxidant protein Sestrin 2 (Sesn2) blocks the ROS-induced neuropathic pain processing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 42 publications
2
43
1
Order By: Relevance
“…Similar studies in macrophages have shown that upregulation of SESN2 protects against H 2 O 2 -induced Prx overoxidation (38,46). In the nervous system SESN2 has been found to control ROS-dependent neuropathic pain signaling after peripheral nerve injury (47) and putatively p53-mediated antioxidant function in the retina (48). SESN2 is also needed for resveratrol, an active component in red wine, to inhibit LXR␣-mediated hepatic lipogenesis (49).…”
Section: Discussionmentioning
confidence: 85%
“…Similar studies in macrophages have shown that upregulation of SESN2 protects against H 2 O 2 -induced Prx overoxidation (38,46). In the nervous system SESN2 has been found to control ROS-dependent neuropathic pain signaling after peripheral nerve injury (47) and putatively p53-mediated antioxidant function in the retina (48). SESN2 is also needed for resveratrol, an active component in red wine, to inhibit LXR␣-mediated hepatic lipogenesis (49).…”
Section: Discussionmentioning
confidence: 85%
“…ROS are required for the development and maintenance of neuropathic pain, which indicated that the Sesns may protect against the neuropathic pain. In spared nerve injury model, a well characterized model of neuropathic pain, researchers found that the expression of Sesn2, but not Sesn1 or Sesn3, was up-regulated in sciatic nerves [52]. Then, they found that Sesn2 knockout ( Sesn2 –/– ) mice exhibited considerably increased latephase neuropathic pain behavior.…”
Section: Sesns In the Nervous Systemmentioning
confidence: 99%
“…Then, they found that Sesn2 knockout ( Sesn2 –/– ) mice exhibited considerably increased latephase neuropathic pain behavior. The increased ROS levels and increased expression of activating transcription factor 3 may contribute to the exacerbated neuropathic pain behavior in Sesn2 –/– mice [52]. In PC12 cells, a widely used neuron-like cell model for studying neurotoxicity and neuroprotection, researchers found that the expression of Sesn2 was induced by H 2 O 2 in a time-dependent and dose-dependent manner through the c-Jun NH (2)-terminal kinase (JNK)/c-Jun pathway [53].…”
Section: Sesns In the Nervous Systemmentioning
confidence: 99%
“…For example, a recent report revealed the protective effect of sestrin2 induction against neurotoxicity associated with MPP + , a mitochondrial complex I inhibitor, in neuroblastoma SH-SY5Y cells [17]. Sestrin2 also controls reactive oxygen species (ROS)-dependent neuropathic pain signaling after peripheral nerve injury [18]. Together, these findings point to the neuroprotective potential of sestrin2, at least in part via attenuation of oxidative stress, in the experimental models mimicking neurodegeneration.…”
Section: Introductionmentioning
confidence: 97%